Prospective cold metal working and analysis of deformation susceptibility of CuMg alloys with high magnesium content - Strzępek, Paweł; Zasadzińska, Małgorzata (Scientific reports, 2024)
Metal alloys designated for cold metal working exhibit much higher strength properties than pure materials due to solid-solution hardening. However, with the increase of mechanical properties its plasticity and workability decreases. Constant development and demand in this area has led to research on many copper alloys, such as copper alloys with high content of magnesium which were never tested before. The limitations regarding cold metal working of CuMg alloys is the main objective of this paper. Here we show that the tested materials exhibit much higher mechanical properties than currently used as electric conductors and carrying-conducting equipment materials such as pure copper, aluminum, M63 brass or CuNiSi alloy. The results were obtained using Hollomon relation, Considére criterion, Gubkin method and hardness measurements. It lead to assessing the prospective cold metal working of CuMg alloys with 2 wt% of magnesium up to 4 wt% of magnesium. The test range included upsetting with 10–50% of cold deformation. It provided the results on evolution of mechanical properties and deformability of tested alloys. Additional information was provided based on the alloys subjected to 50% of strain. The results have proven that as the amount of magnesium increased so did the assessed values, however, it was also linked with increasing friction coefficient. Measured hardness was 2 times higher and calculated Ultimate Tensile Strength (UTS) was even 2.5 times higher in reference to pure copper in the as-cast state. However, with magnesium content at 3.6 wt% or higher, the elevated amount of α + β phase causes brittleness making it impossible to subject these materials to cold metal working processes. We anticipate our assay to be a starting point for more sophisticated models and experimental research concerning cold metal working processes of CuMg alloys of high-strength, which may lead to developing novel and promising set of alloys.